Bayesian Modeling of the Clovis and Folsom Radiocarbon Records Indicates a 200-Year Multigenerational Transition. Issue 3 (July 2022) - Buchanan, Briggs; Kilby, J. David; LaBelle, Jason M.; Surovell, Todd A.; Holland-Lulewicz, Jacob; Hamilton, Marcus J.
Abstract : An enduring problem in North American archaeology concerns the nature of the transition between the Clovis and Folsom Paleoindian complexes in the West. Traditional models indicate a temporal hiatus between the two complexes implying that Folsom was a population replacement for Clovis. Alternatively, if Folsom was an innovation that occurred within Clovis populations and subsequently spread, we would expect to see a temporal overlap. Here, we test these hypotheses using high-quality radiocarbon dates and Bayesian statistics to infer the temporal boundaries of the complexes. We show that the Folsom complex initially appears between 12, 900 and 12, 740 cal BP, whereas Clovis disappears between 12, 720 and 12, 490 cal BP . Therefore, Folsom may have appeared about 200 years before Clovis disappeared, and so the two complexes likely co-occurred in the West for nearly eight generations. This finding suggests that Folsom was a successful adaptive innovation that diffused through the western Clovis population, eventually going to fixation over multiple generations.